Preparation method of 1, 4-dioxane

By impregnating the SO42-/HTaMoO6 catalyst prepared by HTaMoO6 using H2SO4 solution, the problems of many by-products and high production costs in the traditional 1,4-dioxane preparation method are solved, and the 1,4-dioxane preparation is achieved with high efficiency and good selectivity, which is suitable for large-scale production.

CN119528874AActive Publication Date: 2025-02-28DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311105115.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-02-28
Estimated Expiration
2043-08-29

AI Technical Summary

Technical Problem

The traditional 1,4-dioxane preparation method has problems such as many by-products, complicated post-processing, high corrosion of equipment, difficult product refining, high production costs and large wastewater discharge.

Method used

SO42-/HTaMoO6 obtained by impregnating HTaMoO6 by H2SO4 solution as a solid acid catalyst was used to prepare 1,4-dioxane.

Benefits of technology

It improves the conversion rate of ethylene glycol and the selectivity of 1,4-dioxane, and has good stability of the catalyst, and the preparation method is stable, controllable, and reproducible, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528874A_ABST
    Figure CN119528874A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of 1, 4-dioxane, which comprises the following steps: carrying out contact reaction on ethylene glycol and a catalyst to obtain 1, 4-dioxane; the catalyst is SO4 < 2-> / HTaMoO6. The catalyst provided by the invention is applied to a reaction for preparing 1, 4-dioxane through an ethylene glycol dehydration reaction, so that the conversion rate of ethylene glycol and the selectivity of the generated 1, 4-dioxane are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a method for preparing 1,4-dioxane, and belongs to the field of chemical industry. Background Art

[0002] 1,4-Dioxane is an excellent solvent widely used in pharmaceutical, paint, petrochemical and other industries. The traditional production method is to synthesize ethylene glycol under the catalysis of sulfuric acid or phosphoric acid. It is reported that heteropolyacids and their salts also have high catalytic activity for the etherification of alcohols. However, these methods not only have many by-products, but also cumbersome post-processing, high equipment corrosion, difficult product refining, high production costs and large wastewater discharge.

[0003] In recent years, the development of downstream products of ethylene glycol has considerable economic benefits and significance. Among them, the process of preparing 1,4-dioxane from ethylene glycol has received extensive attention due to its greater competitiveness. Therefore, it is of great significance to develop catalysts with good activity, high selectivity, good stability, low cost and environmental protection.

[0004] Solid acid catalysts have become the focus of researchers due to their many advantages such as high activity, high selectivity and easy separation. There are still few solid acid catalysts reported in the literature for catalyzing the dehydration reaction of ethylene glycol. With the advancement of science and technology and the improvement of people's environmental awareness, in chemical production, a solid acid catalyst with advantages such as recyclability and reuse is gradually replacing traditional proton acid catalysts. Summary of the invention

[0005] The application of the solid acid catalyst in the preparation process of 1,4-dioxane has great significance. The catalyst has good activity, high ethylene glycol conversion rate and 1,4-dioxane selectivity, and good stability.

[0006] According to one aspect of the present application, a method for preparing 1,4-dioxane is provided, the method comprising: contacting ethylene glycol with a catalyst to react to obtain 1,4-dioxane;

[0007] The catalyst is SO4 obtained by impregnating HTaMoO6 with H2SO4 solution 2- / HTaMoO6.

[0008] Optionally, the SO4 2- The preparation method of / HTaMoO6 comprises the following steps:

[0009] (1) subjecting a solid acid catalyst to a proton exchange reaction in an acid solution, and drying I to obtain HTaMoO6;

[0010] (2) impregnating HTaMoO6 with H2SO4 solution, drying II, and calcining to obtain the SO4 2- / HTaMoO6;

[0011] The solid acid catalyst is KTaMoO6 or LiTaMoO6.

[0012] Optionally, in step (2), the solid-liquid ratio of the HTaMoO6 and H2SO4 solutions is 1:20 to 30.

[0013] Optionally, the solid-to-liquid ratio of the HTaMoO6 to H2SO4 solution is selected from any value among 1:20, 1:25, 1:30 or any range value between the two.

[0014] Optionally, in step (2), the concentration of the H2SO4 solution is 0.1 to 2M.

[0015] Optionally, the concentration of the H2SO4 solution is selected from any value among 0.1M, 0.3M, 0.5M, 0.7M, 0.9M, 1.1M, 1.3M, 1.5M, 1.7M, 2M or any range between two values.

[0016] Optionally, in step (1), the solid-liquid ratio of the solid acid catalyst to the acid solution is 1:20 to 30.

[0017] Optionally, the solid-liquid ratio of the solid acid catalyst to the acid solution is selected from any value among 1:20, 1:25, 1:30 or any range value between the two;

[0018] Optionally, in step (1), the concentration of the acid solution is 2 to 10M.

[0019] Optionally, the concentration of the acid solution is selected from any value among 2M, 3M, 4M, 5M, 6M, 7M, 8M, 9M, 10M or any range between two values.

[0020] Optionally, in step (1), the acid solution is selected from nitric acid and / or hydrochloric acid.

[0021] Optionally, in step (1), the proton exchange reaction time is 24 to 96 hours.

[0022] Optionally, the time of the proton exchange reaction is selected from any value of 24 hours, 36 hours, 48 ​​hours, 60 hours, 72 hours, 84 hours, 96 hours, or any range between two thereof;

[0023] Optionally, the temperature of the drying I is 80° C. to 110° C., and the time of the drying I is 2 hours to 5 hours.

[0024] Optionally, the drying temperature I is selected from any value among 80°C, 90°C, 100°C, 110°C or any range between the two.

[0025] Optionally, the drying time I is selected from any value among 2 hours, 3 hours, 4 hours, 5 hours, or any range value between the two.

[0026] Optionally, the immersion time is 4 to 24 hours.

[0027] Optionally, the immersion time is selected from any value of 4 hours, 8 hours, 12 hours, 16 hours, 20 hours, 24 hours, or any range between two of them.

[0028] Optionally, in step (2), the temperature of drying II is 80° C. to 110° C., and the time of drying II is 2 hours to 5 hours.

[0029] Optionally, the drying temperature II is selected from any value among 80°C, 90°C, 100°C, 110°C, or any range therebetween.

[0030] Optionally, the drying time II is selected from any value among 2 hours, 3 hours, 4 hours, 5 hours, or any range value therebetween.

[0031] Optionally, the calcination temperature is 400° C. to 600° C., and the calcination time is 3 hours to 6 hours.

[0032] Optionally, the calcination temperature is selected from any value of 400°C, 450°C, 500°C, 550°C, 600°C or any range therebetween.

[0033] Optionally, the calcination time is selected from any value of 3 hours, 4 hours, 5 hours, 6 hours, or any range between the two.

[0034] Optionally, the reaction temperature is 100-200°C; the N2 flow rate in the reaction is 0-30 ml / min; the mass space velocity of the reaction is 0.2-2 h -1 ;

[0035] Optionally, the reaction temperature is selected from any value of 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C or any range therebetween.

[0036] Optionally, the N2 flow rate in the reaction is any value among 0ml / min, 5ml / min, 10ml / min, 15ml / min, 20ml / min, 25ml / min, 30ml / min or any range value between two of them.

[0037] Optionally, the mass space velocity of the reaction is 0.2h -1 、0.4h -1 、0.6h -1 、0.8h -1 , 1.0h -1 , 1.2h -1 , 1.4h -1 , 1.6h -1 , 1.8h -1 , 2.0h -1 Any value in between or any range of values ​​between them.

[0038] In this application, the SO4 2- The preparation method of / HTaMoO6 comprises the following steps:

[0039] Prepare KTaMoO6 (LiTaMoO6) by a molten salt method, then subject the KTaMoO6 (LiTaMoO6) to a proton exchange reaction in an acid solution, wash, and dry to obtain the HTaMoO6;

[0040] The H2SO4 solution is used to impregnate HTaMoO6, filter, dry and calcine. The solid acid catalyst SO4 is obtained. 2- / HTaMoO6.

[0041] Among them, the specific steps of preparing KTaMoO6 (LiTaMoO6) by molten salt method include:

[0042] 1) mixing a tantalum source, a molybdenum source, a molten salt and a solvent, grinding after ultrasonication, and drying to obtain a mixture;

[0043] 2) calcining the mixture obtained in step 1), washing, and obtaining KTaMoO6 (LiTaMoO6);

[0044] The tantalum source is selected from at least one of tantalum pentoxide and tantalum powder;

[0045] The molybdenum source is selected from at least one of molybdenum oxide and molybdenum powder;

[0046] The molten salt is K2CO3 or LiCO3.

[0047] The molar ratio of the tantalum source to the molybdenum source is 1:(0.9-2);

[0048] Optionally, the molar ratio of the tantalum source to the molybdenum source is any value of 1:0.9, 1:1, 1:1.9, 1:2, or a range value between any two of them.

[0049] Optionally, the molar ratio of the tantalum source to the molten salt is (1-2): (0.9-2).

[0050] Optionally, the molar ratio of the tantalum source to the molten salt is any value among 1:0.9, 1:1, 1:1.9, 1:2, 2:0.9, 2:1, or a range value between any two of them.

[0051] Optionally, the solvent is one of methanol, ethanol and acetone.

[0052] Optionally, the drying temperature in step 1) is 80° C. to 110° C., and the drying time is 2 hours to 5 hours.

[0053] Optionally, the drying temperature is any value among 80°C, 90°C, 100°C, 110°C, or a range between any two of them.

[0054] Optionally, the drying time is any value among 2 hours, 3 hours, 4 hours, 5 hours, or a range value between any two of them.

[0055] Optionally, the calcination temperature in step 2) is 600° C. to 1200° C., and the calcination time is 12 hours to 48 hours.

[0056] Optionally, the calcination temperature is any value of 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, or a range between any two values;

[0057] Optionally, the calcination time is any value of 12 hours, 24 hours, 36 hours, 48 ​​hours, or any range between the two.

[0058] The beneficial effects of this application include:

[0059] 1) The solid acid catalyst SO4 provided in this application 2- / HTaMoO6 can be used in the dehydration reaction of ethylene glycol to prepare 1,4-dioxane, and can improve the conversion rate of ethylene glycol and the selectivity of the generated 1,4-dioxane.

[0060] 2) The solid acid catalyst SO4 provided in this application 2- The preparation method of / HTaMoO6 is stable, controllable and reproducible.

[0061] 3) The method for preparing 1,4-dioxane by dehydrating ethylene glycol provided in the present application uses the solid acid catalyst provided in the present application, has a fast reaction speed and a high yield, and can be applied to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 This is the X-ray powder diffraction pattern of HTaMoO6 during the synthesis of catalyst 1 in Example 1 of the present application. DETAILED DESCRIPTION

[0063] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0064] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0065] The gas chromatograph is a 7890B gas chromatograph from Agilent.

[0066] In the examples of this application, the conversion rate and selectivity are calculated as follows:

[0067] The conversion rate and selectivity calculation formula in the examples of the present application are as follows (with ethylene glycol conversion rate as the evaluation index):

[0068] Ethylene glycol conversion rate = (initial carbon number of ethylene glycol - carbon number of ethylene glycol in the product) * 100 / initial mole number of ethylene glycol

[0069] 1,4-dioxane selectivity = carbon number of 1,4-dioxane*100 / ∑(carbon number of 1,4-dioxane+carbon number of other products).

[0070] XRD Characterization:

[0071] The catalyst 1 was subjected to X-ray diffractometer analysis using a Miniflex 600 instrument with a Cu target. # Powder diffraction showed that the diffraction peaks of HTaMoO6 during the synthesis of catalyst 1 were consistent with the characteristic peaks of HTaMoO6 (such as Figure 1 shown).

[0072] Example 1 Preparation of Catalyst

[0073] Tantalum pentoxide and molybdenum oxide in a molar ratio of 1:2 are mixed with molten salt K2CO3 in an ethanol solution (the molar ratio of tantalum source to molten salt is 1:1), ground and mixed after ultrasonic treatment, and placed in a 100°C oven to dry for 4 hours; then placed in a high-temperature furnace and calcined at 1000°C for 24 hours to obtain a KTaMoO6 sample. The KTaMoO6 sample is mixed with nitric acid (concentration 6M) at a solid-liquid ratio of 1:20 and subjected to a proton exchange reaction for 72 hours, and then placed in a 100°C oven to dry for 4 hours; HTaMoO6 (solid-liquid ratio 1:20) is impregnated with 0.5M H2SO4 solution for 8 hours, filtered, placed in a 100°C oven to dry for 4 hours, and then calcined at 500°C for 3 hours to obtain a solid acid catalyst 1, namely SO4 2- / HTaMoO6. Figure 1 The peaks of the X-ray powder diffraction pattern can be seen in the figure, which are consistent with the characteristics of HTaMoO6.

[0074] Example 2

[0075] Tantalum pentoxide and molybdenum powder in a molar ratio of 1:1.9 are mixed with molten salt LiCO3 in a methanol solution (the molar ratio of tantalum source to molten salt is 1:1.9), ground and mixed after ultrasonic treatment, and placed in a 90°C oven to dry for 5 hours; then placed in a high-temperature furnace and calcined at 1200°C for 12 hours to obtain a LiTaMoO6 sample. The LiTaMoO6 sample is mixed with hydrochloric acid (concentration 8M) at a solid-liquid ratio of 1:25, and then subjected to a proton exchange reaction for 48 hours, and then placed in a 90°C oven to dry for 5 hours; HTaMoO6 (solid-liquid ratio 1:25) is impregnated with 0.9M H2SO4 solution for 12 hours, filtered, placed in a 90°C oven to dry for 5 hours, and then calcined at 450°C for 5 hours to obtain a solid acid catalyst 2, namely SO4 2- / HTaMoO6.

[0076] Example 3

[0077] Tantalum powder and molybdenum oxide in a molar ratio of 1:1 are mixed with molten salt K2CO3 in an acetone solution (the molar ratio of tantalum source to molten salt is 2:1), ground and mixed after ultrasonic treatment, and placed in a 110°C oven to dry for 2 hours; then placed in a high-temperature furnace and calcined at 800°C for 36 hours to obtain a KTaMoO6 sample. The KTaMoO6 sample is mixed with nitric acid (concentration 4M) at a solid-liquid ratio of 1:30, and then subjected to a proton exchange reaction for 84 hours, and then placed in a 110°C oven to dry for 2 hours; HTaMoO6 (solid-liquid ratio 1:30) is impregnated with 0.7M H2SO4 solution for 16 hours, filtered, placed in a 110°C oven to dry for 2 hours, and then calcined at 550°C for 4 hours to obtain a solid acid catalyst 3, namely SO4 2- / HTaMoO6.

[0078] Example 4

[0079] Tantalum powder and molybdenum powder with a molar ratio of 1:0.9 are mixed with molten salt LiCO3 in an ethanol solution (the molar ratio of tantalum source to molten salt is 1:0.9), ground and mixed after ultrasonic treatment, and placed in an oven at 80°C for drying for 3 hours; then placed in a high-temperature furnace at 900°C for calcination for 12 hours to obtain a LiTaMoO6 sample. The LiTaMoO6 sample is mixed with hydrochloric acid (concentration 10M) at a solid-liquid ratio of 1:20, and then subjected to a proton exchange reaction for 24 hours, and then placed in an oven at 80°C for drying for 3 hours; HTaMoO6 (solid-liquid ratio 1:20) is impregnated with 0.3M H2SO4 solution for 20 hours, filtered, placed in an oven at 80°C for drying for 3 hours, and then calcined at 600°C for 3 hours to obtain a solid acid catalyst 4, namely SO4 2- / HTaMoO6.

[0080] Example 5

[0081] Tantalum pentoxide and molybdenum oxide in a molar ratio of 1:2 are mixed with molten salt K2CO3 in an ethanol solution (the molar ratio of tantalum source to molten salt is 1:1), ground and mixed after ultrasonic treatment, and placed in a 100°C oven to dry for 3 hours; then placed in a high-temperature furnace at 700°C for calcination for 48 hours to obtain a KTaMoO6 sample. The KTaMoO6 sample is mixed with nitric acid (concentration 7M) at a solid-liquid ratio of 1:20 and subjected to a proton exchange reaction for 72 hours, and then placed in a 100°C oven to dry for 3 hours; HTaMoO6 (solid-liquid ratio 1:20) is impregnated with 0.5M H2SO4 solution for 8 hours, filtered, placed in a 100°C oven to dry for 3 hours, and then calcined at 400°C for 6 hours to obtain a solid acid catalyst 5, namely SO4 2- / HTaMoO6.

[0082] Example 6

[0083] Tantalum powder and molybdenum oxide in a molar ratio of 1:1 are mixed with molten salt K2CO3 in a methanol solution (the molar ratio of tantalum source to molten salt is 2:0.9), ground and mixed after ultrasonic treatment, and placed in a 110°C oven to dry for 5 hours; then placed in a high-temperature furnace at 1100°C for calcination for 24 hours to obtain a KTaMoO6 sample. The KTaMoO6 sample is mixed with hydrochloric acid (concentration 5M) at a solid-liquid ratio of 1:25, and then subjected to a proton exchange reaction for 60 hours, and then placed in a 110°C oven to dry for 5 hours; HTaMoO6 (solid-liquid ratio 1:25) is impregnated with a 1.1M H2SO4 solution for 4 hours, filtered, placed in a 110°C oven to dry for 5 hours, and then calcined at 500°C for 3 hours to obtain a solid acid catalyst 6, namely SO4 2- / HTaMoO6.

[0084] Example 7

[0085] Tantalum powder and molybdenum powder with a molar ratio of 1:0.9 are mixed with molten salt LiCO3 in an ethanol solution (the molar ratio of tantalum source to molten salt is 1:0.9), ground and mixed after ultrasonic treatment, and placed in a 90°C oven to dry for 4 hours; then placed in a high-temperature furnace at 600°C for calcination for 12 hours to obtain a LiTaMoO6 sample. The LiTaMoO6 sample is mixed with hydrochloric acid (concentration 3M) ​​at a solid-liquid ratio of 1:30, and then subjected to a proton exchange reaction for 96 hours, and placed in a 90°C oven to dry for 4 hours; HTaMoO6 (solid-liquid ratio 1:30) is impregnated with a 1.3M H2SO4 solution for 4 hours, filtered, placed in a 90°C oven to dry for 4 hours, and then calcined at 550°C for 4 hours to obtain a solid acid catalyst 7, namely SO4 2- / HTaMoO6.

[0086] Example 8

[0087] Tantalum pentoxide and molybdenum powder in a molar ratio of 1:1.9 were mixed with molten salt LiCO3 in a methanol solution (the molar ratio of tantalum source to molten salt was 1:2), ground and mixed after ultrasonic treatment, and placed in an oven at 80°C for 2 hours for drying; then placed in a high-temperature furnace at 1000°C for calcination for 36 hours to obtain a LiTaMoO6 sample. The LiTaMoO6 sample was mixed with nitric acid (concentration 2M) at a solid-liquid ratio of 1:20 and subjected to a proton exchange reaction for 60 hours, and then placed in an oven at 80°C for 2 hours for drying; HTaMoO6 (solid-liquid ratio 1:20) was impregnated with a 1.7M H2SO4 solution for 12 hours, filtered, placed in an oven at 80°C for drying for 2 hours, and then calcined at 600°C for 5 hours to obtain a solid acid catalyst 8, namely SO4 2- / HTaMoO6.

[0088] Example 9

[0089] Tantalum powder and molybdenum oxide in a molar ratio of 1:1 are mixed with molten salt K2CO3 in an ethanol solution (the molar ratio of tantalum source to molten salt is 2:1), ground and mixed after ultrasonic treatment, and placed in a 100°C oven to dry for 5 hours; then placed in a high-temperature furnace and calcined at 1200°C for 24 hours to obtain a KTaMoO6 sample. The KTaMoO6 sample is mixed with hydrochloric acid (concentration 9M) at a solid-liquid ratio of 1:25, and then subjected to a proton exchange reaction for 72 hours, and then placed in a 100°C oven to dry for 5 hours; HTaMoO6 (solid-liquid ratio 1:25) is impregnated with a 2M H2SO4 solution for 16 hours, filtered, placed in a 100°C oven to dry for 5 hours, and then calcined at 450°C for 3 hours to obtain a solid acid catalyst 9, namely SO4 2- / HTaMoO6.

[0090] Example 10

[0091] Tantalum pentoxide and molybdenum oxide in a molar ratio of 1:2 are mixed with molten salt K2CO3 in an acetone solution (the molar ratio of tantalum source to molten salt is 1:1), ground and mixed after ultrasonic treatment, and placed in a 110°C oven to dry for 3 hours; then placed in a high-temperature furnace and calcined at 700°C for 12 hours to obtain a KTaMoO6 sample. The KTaMoO6 sample is mixed with nitric acid (concentration 6M) at a solid-liquid ratio of 1:20 and subjected to a proton exchange reaction for 48 hours, and then placed in a 110°C oven to dry for 3 hours; HTaMoO6 (solid-liquid ratio 1:20) is impregnated with a 1.5M H2SO4 solution for 8 hours, filtered, placed in a 110°C oven to dry for 3 hours, and then calcined at 400°C for 6 hours to obtain a solid acid catalyst 10, namely SO4 2- / HTaMoO6.

[0092] Embodiment 11

[0093] Tantalum powder and molybdenum powder in a molar ratio of 1:1 were mixed with molten salt LiCO3 in an ethanol solution (the molar ratio of tantalum source to molten salt was 1:0.9), ground and mixed after ultrasonic treatment, and placed in an oven at 80°C for 2 hours for drying; then placed in a high-temperature furnace at 900°C for calcination for 48 hours to obtain a LiTaMoO6 sample. The LiTaMoO6 sample was mixed with nitric acid (concentration 4M) at a solid-liquid ratio of 1:30, and then subjected to a proton exchange reaction for 36 hours, and then placed in an oven at 80°C for 2 hours for drying; HTaMoO6 (solid-liquid ratio 1:30) was impregnated with 0.1M H2SO4 solution for 8 hours, filtered, placed in an oven at 80°C for 2 hours for drying, and then calcined at 500°C for 5 hours to obtain a solid acid catalyst 11, namely SO4 2- / HTaMoO6.

[0094] Example 12

[0095] Tantalum powder and molybdenum oxide in a molar ratio of 1:0.9 are mixed with molten salt K2CO3 in an ethanol solution (the molar ratio of tantalum source to molten salt is 2:0.9), ground and mixed after ultrasonic treatment, and placed in a 110°C oven to dry for 4 hours; then placed in a high-temperature furnace for calcination at 1000°C for 36 hours to obtain a KTaMoO6 sample. The KTaMoO6 sample is mixed with hydrochloric acid (concentration 8M) at a solid-liquid ratio of 1:20, and then subjected to a proton exchange reaction for 84 hours, and then placed in a 110°C oven to dry for 4 hours; HTaMoO6 (solid-liquid ratio 1:20) is impregnated with 0.5M H2SO4 solution for 20 hours, filtered, placed in a 110°C oven to dry for 4 hours, and then calcined at 450°C for 4 hours to obtain a solid acid catalyst 12, namely SO4 2- / HTaMoO6.

[0096] Example 13

[0097] Tantalum pentoxide and molybdenum powder in a molar ratio of 1:1.9 are mixed with molten salt LiCO3 in a methanol solution (the molar ratio of tantalum source to molten salt is 1:1.9), ground and mixed after ultrasonic treatment, and placed in a 90°C oven to dry for 3 hours; then placed in a high-temperature furnace at 800°C for calcination for 24 hours to obtain a LiTaMoO6 sample. The LiTaMoO6 sample is mixed with hydrochloric acid (concentration 7M) at a solid-liquid ratio of 1:30, and then subjected to a proton exchange reaction for 96 hours, and placed in a 90°C oven to dry for 3 hours; HTaMoO6 (solid-liquid ratio 1:30) is impregnated with 0.9M H2SO4 solution for 8 hours, filtered, placed in a 90°C oven to dry for 3 hours, and then calcined at 550°C for 5 hours to obtain a solid acid catalyst 13, namely SO4 2- / HTaMoO6.

[0098] Embodiment 14

[0099] Tantalum pentoxide and molybdenum powder in a molar ratio of 1:2 are mixed with molten salt K2CO3 in an ethanol solution (the molar ratio of tantalum source to molten salt is 1:1), ground and mixed after ultrasonic treatment, and placed in an oven at 80°C for 2 hours for drying; then placed in a high-temperature furnace at 600°C for calcination for 36 hours to obtain a KTaMoO6 sample. The KTaMoO6 sample is mixed with nitric acid (concentration 5M) at a solid-liquid ratio of 1:25, and then subjected to a proton exchange reaction for 24 hours, and then placed in an oven at 80°C for 2 hours for drying; HTaMoO6 (solid-liquid ratio 1:25) is impregnated with 0.7M H2SO4 solution for 12 hours, filtered, placed in an oven at 80°C for 2 hours for drying, and then calcined at 600°C for 3 hours to obtain a solid acid catalyst 14, namely SO4 2- / HTaMoO6.

[0100] Embodiment 15

[0101] Tantalum powder and molybdenum oxide in a molar ratio of 1:0.9 are mixed with molten salt LiCO3 in an acetone solution (the molar ratio of tantalum source to molten salt is 1:0.9), ground and mixed after ultrasonic treatment, and placed in a 90°C oven to dry for 4 hours; then placed in a high-temperature furnace and calcined at 1000°C for 12 hours to obtain a LiTaMoO6 sample. The LiTaMoO6 sample is mixed with hydrochloric acid (concentration 9M) at a solid-liquid ratio of 1:20 and subjected to a proton exchange reaction for 72 hours, and then placed in a 90°C oven to dry for 4 hours; HTaMoO6 (solid-liquid ratio 1:20) is impregnated with a 1.1M H2SO4 solution for 16 hours, filtered, placed in a 90°C oven to dry for 4 hours, and then calcined at 400°C for 4 hours to obtain a solid acid catalyst 15, namely SO4 2- / HTaMoO6.

[0102] Example 16

[0103] Tantalum pentoxide and molybdenum oxide in a molar ratio of 1:1.9 are mixed with molten salt K2CO3 in a methanol solution (the molar ratio of tantalum source to molten salt is 1:1), ground and mixed after ultrasonic treatment, and placed in a 100°C oven to dry for 5 hours; then placed in a high-temperature furnace at 1100°C for calcination for 48 hours to obtain a KTaMoO6 sample. The KTaMoO6 sample is mixed with nitric acid (concentration 6M) at a solid-liquid ratio of 1:30, and then subjected to a proton exchange reaction for 60 hours, and then placed in a 100°C oven to dry for 5 hours; HTaMoO6 (solid-liquid ratio 1:30) is impregnated with 0.3M H2SO4 solution for 8 hours, filtered, placed in a 100°C oven to dry for 5 hours, and then calcined at 500°C for 6 hours to obtain a solid acid catalyst 16, namely SO4 2- / HTaMoO6.

[0104] Comparative Example 1

[0105] Tantalum pentoxide and molybdenum oxide in a molar ratio of 1:2 are mixed with molten salt K2CO3 in an ethanol solution (the molar ratio of tantalum source to molten salt is 1:1), ground and mixed after ultrasonic treatment, and placed in a 100°C oven to dry for 4 hours; then placed in a high-temperature furnace and calcined at 1000°C for 24 hours to obtain a KTaMoO6 sample. The KTaMoO6 sample is mixed with nitric acid (concentration 6M) at a solid-liquid ratio of 1:20, and then a proton exchange reaction is carried out for 72 hours, and then placed in a 100°C oven to dry for 4 hours to obtain HTaMoO6.

[0106] Embodiment 17

[0107] The catalysts 1, 5, 8, 11, 13 and 16 prepared in Examples 1, 5, 8, 11, 13 and 16 were used to carry out the dehydration of ethylene glycol to prepare 1,4-dioxane, and the reaction parameters were changed. After the reaction was stable (reaction for 6 hours), the reaction raw materials and products were analyzed by gas chromatography online. The reaction results are shown in Table 1.

[0108] Gas chromatography characterization:

[0109] The composition of the ethylene glycol dehydration reaction products was analyzed using an Agilent 7890B gas chromatograph (FID detector, FFAP capillary column).

[0110] Table 1

[0111]

[0112]

[0113] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing 1,4-dioxane, characterized in that: The preparation method comprises: contacting ethylene glycol with a catalyst to react to obtain 1,4-dioxane; The catalyst is SO4 obtained by impregnating HTaMoO6 with H2SO4 solution 2- / HTaMoO6.

2. The preparation method according to claim 1, characterized in that: The SO4 2- The preparation method of / HTaMoO6 comprises the following steps: (1) subjecting a solid acid catalyst to a proton exchange reaction in an acid solution, and drying I to obtain HTaMoO6; (2) impregnating HTaMoO6 with H2SO4 solution, drying II, and calcining to obtain the SO4 2- / HTaMoO6; The solid acid catalyst is KTaMoO6 or LiTaMoO6.

3. The preparation method according to claim 2, characterized in that: In the step (2), the solid-to-liquid ratio of the HTaMoO6 and H2SO4 solutions is 1:20 to 30.

4. The preparation method according to claim 2, characterized in that: In the step (2), the concentration of the H2SO4 solution is 0.1 to 2M.

5. The preparation method according to claim 2, characterized in that: In the step (1), the solid-to-liquid ratio of the solid acid catalyst to the acid solution is 1:20-30.

6. The preparation method according to claim 2, characterized in that: In the step (1), the concentration of the acid solution is 2 to 10 M; Preferably, in step (1), the acid solution is selected from nitric acid and / or hydrochloric acid.

7. The preparation method according to claim 2, characterized in that: In the step (1), the proton exchange reaction time is 24 to 96 hours; Preferably, the temperature of the drying I is 80° C. to 110° C., and the time of the drying I is 2 hours to 5 hours.

8. The preparation method according to claim 2, characterized in that: In the step (2), the immersion time is 4 to 24 hours.

9. The preparation method according to claim 2, characterized in that: In the step (2), the temperature of the drying II is 80°C to 110°C, and the drying II time is 2 hours to 5 hours; Preferably, the calcination temperature is 400° C. to 600° C., and the calcination time is 3 hours to 6 hours.

10. The preparation method according to claim 1, characterized in that: The reaction temperature is 100-200°C; The N2 flow rate in the reaction is 0-30 ml / min; The mass space velocity of the reaction is 0.2 to 2 h -1 .

Citation Information

Patent Citations

  • Method for preparing 1, 4-dioxane

    CN105985312A

  • Solid acid catalyst and method for preparing 1,4-dioxane by using solid acid catalyst

    CN106345495A

  • Method for catalytically depolymerizing lignin

    CN108014782A

  • Preparation method of 1,4-dioxane produced by dehydrating ethylene glycol

    CN108101882A

  • Method for preparing 1,4-dioxane through continuous catalytic conversion

    CN108129444A